Pemetaan Sebaran Titik Parkir Menggunakan Software ARCGIS Student Version Kecamatan Langsa Baro - Siti Zakia; Wan Alamsyah; Defry Basrin (Journal of Innovative and Creativity, 2026)
Langsa baro district is one of the only district in langsa city. Langsa baro's equity has 12 (twelve) villages in the midst of rapid growth in sertai with population growth that is influential in increasing number of vehicles. This is because langsa baro district has such public places as schools, hospitals and offices that cause daily traffic flow. Rapid population growth and the ownership of motor vehicles result in parking land limitations and increased demand for parking lots. The assessment aims to find out the formation of a parking spot in langsa baro district that was then visualized through the gis map and to identify the parking characteristics of the rahmah mosque in tunong paya village as the densest parking site in langsa baro district. The method employed in the study was to survey the location coordinates for parking and to calculate the number of characteristics of the parking space. Studies show that 137 park-drop levels are in langsa baro district, with 60 special parking spots and 76 public parking spots. And characteristic analysis of the parking space at the maximum intensity of the parking lot at the rahmah village of bujok in the ong ong boong decline by langsa baro temple with a maximum accumulated value of 82 motorcycles and 16 cars, the parking lot of 198 and 25 volumes for car parking, the parking index for 95% and the index for car parking of 280%, the parking capacity for 1651 SRP for cars.